Вплив фітогормонів на вкорінення кімнатних рослин - Бугайчук, Анна; Сеньків, Ірина; Андреєва, Валентина; Bugaichuk, Anna; Sen’kiv, Iryna; Andreyeva, Valentyna (Східноєвропейський національний університет імені Лесі Українки, 2014)
Досліджено фітогормони – стимулятори ризогенезу листкових та стеблових живців кімнатних рослин, а також вплив ауксинів на вкорінення окремих видів роду Begonia та Saintpaulia ionantha, Hibiscus rosa-sinensis, Dracaena fragrans, Boehmeria macrophylla. The phytohormones − stimulants of root process of leaf and stem cuttings of house plants and the influence of auxins on rooting of different types of Begonia, Saintpaulia ionantha, Hibiscus rosa-sinensis, Dracaena fragrans and Boehmeria macrophylla were investigated. The duration of rooting of leaf cuttings in autumn is ranges from 23 to 42 days (for Begonia Rex and Saintpaulia ionantha respectively). The duration of rooting of stem cuttings is slightly higher and it is 32 days for Boehmeria macrophylla, 36 days Dracaena fragrans and 45 days for Hibiscus rosa-sinensis. The best stimulant of rooting for leaf cuttings of Begonia boweri sort “Black velvet” and Begonia Rex is the IAA (100 mg/l). Leaf cuttings tuberous begonias (Begonia × Tuberhybrida, sorts “Camelia” and “Picotee”) are difficult to reproduce even when stimulants of rooting were using. Number of rooted cuttings tuberous begonia “Camellia” and “Pikotee” are varieties from 25−30 %, with very weak integrated index of rooting (0−7 %). Rooting of green stem cuttings of Boehmeria macrophylla is satisfactory by using all experimental solutions. The best stimulant of rooting of stem cuttings of Dracaena fragrans is the mixture IAA + IOA (100 mg/l) and IOA (100 mg/l).The index of rooting of Hibiscus rosa-sinensis is good when we were using solution IAA and satisfactory solution by using IOA.
Phytohormones Effect on Root Process of Houseplants
Keywords: фітогормони; ризогенез; інтенсивність укорінення; успішність укорінення; plant hormones; rooting index; rooting success